Helical tomotherapy for cancer treatment: a rapid health technology assessment. Issue 3 (August 2014) - Yang, Zong Xia; Shen, Jian Tong; Li, You Ping; Zhao, Kun; Shi, Cheng Hu; Xiao, Yue; Yu, Jia Jie; Guo, Wu Dong; Li, Cui Cui; Wang, Ying Qiang; Li, Xiang Lian; on behalf of the Rapid Health Technology Assessment Working Group of Chinese Evidence‐Based Medicine Centre
Abstract Objectives Helical tomotherapy (HT) can be applied to treat complex malignant cancer with high‐precise radiotherapy, and it can reduce the damage to normal tissues and improve treatment effects. But the procurement of HT must be approved by relevant departments of administration affairs. This study, appointed by the National Health and Family Planning Commission of China and undertook by the National Health Development Research Center and the Chinese Evidence‐Based Medicine Centre, was aimed to rapidly assess the effectiveness, safety, costs, and applicability of HT, so as to provide currently available best evidence for decision‐makers of health policies. Methods We electronically searched databases including PubMed, EMbase, The Cochrane Library, CNKI, WanFang Data, VIP, CBM, and other professional websites. Two reviewer independently screened literature according to the inclusion and exclusion criteria, extracted data, assessed quality, and then performed descriptive analysis. Results (i) We finally included 150 studies, encompassing 5 HTAs, 18 CCTs, and 127 observational studies. (ii) The included HTAs were published during 2006–2009, providing fairly less evidence of low quality and the results of 145 primary studies showed that: HT had been used mainly in the treatments of 14 kinds of cancer, with low total toxicity and high survival rates. Although the quality of the included studies was poor, there was much evidence about prostate cancer, head and neck cancer, nasopharynx cancer, cervical cancer, lung cancer and liver cancer, with enough sample and fairly reliable results in HT efficacy and safety. And (iii) a total of 56 clinical trials were registered in Clinicaltrials.gov, most of which were registered by the occident. Among them, 9 were completed but the results had not been published yet. Conclusions The evidence of this study showed that, HT is safe and effective in clinic. But the abovementioned conclusion needs to be verified by conducting more high‐quality studies with long‐term follow‐up. The costs of HT in procurement, maintenance, and application are high; and the skills, training, and qualification of operators are required. We suggest that the procurement of HT should be reduced; it should be allocated rationally and effectively used after comprehensive assessment in China's cancer epidemiology characteristics, health resource allocation, disease burden, medical service level, etc.; and also high‐quality studies with long‐term follow‐up should be financially supported on the basis of establishing projects, so as to provide local evidence and consistently guide and improve scientific decision‐making.